Efektivitas Bioadsorben dalam Pengolahan Limbah Warna Methyl Orange dengan Menggunakan Kulit Buah Kakao (Theobroma cacao L) - Suhartono, Jono; Fadillah, Fitri Nur; Pratiwi, Vibianti Dwi; Choerudin; Kurniawan, Ronny (Program Studi Teknik Kimia, Universitas Pamulang, 2026)
Cacao (Theobroma cacao L) is a plant that produces 75% of waste in the form of fruit peels. Cacao pod husk contains coarse fiber, cellulose, hemicellulose, and lignin so it has the potential to be used as an adsorbent. Textile liquid waste generally contains dyes that are difficult to decompose and have the potential to pollute the environment, one of which is methyl orange (MO) which is toxic and mutagenic. This study aims to evaluate the effectiveness of cacao peel as a bioadsorbent in the elimination of MO from liquid waste. The adsorption process is carried out using a packed column with a cacao bed weight of 100g. The initial concentration of the MO waste feed used is 5 ppm with an operating temperature at room conditions between 25 - 27oC. In this study, the influence of flow rate and pH was studied. The best results were compared to cacao bioadsorbents activated using the alkaline method. The results showed that the optimal conditions were achieved at a flow rate of 25 ml/min and pH 7 with an adsorption capacity of 19.81 × 10⁻⁵ mg/g. Cacao bioadsorbent with alkaline activation is able to increase the surface area and pore volume of the adsorbent, so that the adsorption capacity increases even though the activation residue has an effect on the chemical oxygen demand (COD) and total suspended solid (TSS) values.